The ability of topical and systemic statins to increase osteogenesis around dental implants: a systematic review of histomorphometric outcomes in animal studies. Issue 8 (August 2018) - Moraschini, V.; Almeida, D.C.F.; Calasans-Maia, J.A.; Diuana Calasans-Maia, M.
Abstract: The purpose of this systematic review was to evaluate the quantitative histomorphometric outcomes of animal studies investigating statins as a pro-osteogenic agent to enhance the osseointegration of dental implants. Some animal studies have suggested a beneficial action of statins on bone tissue. Electronic and manual literature searches, without date or language restriction, ​​were performed by two independent review authors up to February 2017. Eligibility criteria included animal trials quantitatively analysing the pro-osteogenic effect of statins on dental implants. The quality of the included studies was assessed using the ARRIVE guidelines. The search and selection process yielded 12 studies, published between 2004 and 2015. The experimental animals models used were rats and dogs. The statins used in the studies were simvastatin and fluvastatin, which were administered locally or systemically, or applied to the implant surface. All of the selected studies showed a statistically significant positive effect of statins on bone formation around implants. The mean quality assessment score (ARRIVE) of the studies was 11.5 ± 2.27 out of a possible total of 25 points. The histomorphometric data from available preclinical studies suggest a positive effect of statins on increasing osteogenesis around dental implants.